2017
DOI: 10.18203/2320-1770.ijrcog20171395
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress among gravid and its effect on their oral health in Sri Ganganagar, Rajasthan, India

Abstract: Background: The gestation period presents unique stresses that challenges overall psychological adaptation of a women. The present study is designed especially to focus on evaluating the effect of perceived stress on pregnant women and its effect on their oral health.Methods: A cross-sectional study was conducted among 18-30 years old, pregnant women in the Sri Ganganagar city. Prior to the clinical examination a questionnaire was used in order to collect the information which comprised of three parts and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…42,43 Several studies have reported that expecting women with high stress are less likely to show healthy behaviour, such as normal sleep patterns, taking care of their oral and dental hygiene and take precautions for diseases. [44][45][46][47][48] Thus, in addition to the direct negative effects stress has on the health of the child, stress also causes such adverse outcomes by reducing the mother's willingness to practice the required health behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Several studies have reported that expecting women with high stress are less likely to show healthy behaviour, such as normal sleep patterns, taking care of their oral and dental hygiene and take precautions for diseases. [44][45][46][47][48] Thus, in addition to the direct negative effects stress has on the health of the child, stress also causes such adverse outcomes by reducing the mother's willingness to practice the required health behaviour.…”
Section: Discussionmentioning
confidence: 99%